Determinación de plomo, cadmio, mercurio y Bases Volátiles Nitrogenadas Totales (NBVT) en el músculo de tiburón azul Prionace glauca procedente de la zona sur del Perú - Reátegui-Quispe, Andrés; Pariona-Velarde, Daniel (Revista de Biología Marina y Oceanografía, 2020)
Blue shark Prionace glauca is one of the most important elasmobranch species landed and consumed in Peru. Due to its importance as fishery resource, were evaluated lead (Pb), cadmium (Cd), mercury (Hg) and Total Volatile Base Nitrogen (TVBN) in the muscle tissue of 25 specimens, captured in the southern zone of Peruvian sea. These analytes were compared with current regulations and were determined its relationship with sex and total length (TL). We obtained ranges between 0.04-0.25, 0.01-0.04 and 0.09-0.50 mg kg-1 for Pb, Cd and Hg, respectively. TVBN values were between 38.50-94.60 mg TVBN 100 g-1. Analytes did not have differences with TL and gender. Pb was positive correlation with TL, while the Cd, Hg and TVBN did not. This study provides sanitary information of blue shark muscle from Peruvian waters.